Point-of-Care Testing in Burn Patients - Wiegele, Marion; Kozek-Langenecker, Sibylle; Schaden, Eva (Seminars in Thrombosis and Hemostasis, 2017)
Severe burn injury has an impact on the coagulation system, but a unique definition regarding these changes is still missing. The results of conventional coagulation assays (CCAs) measured in daily clinical practice are often interpreted as coagulopathic, which implies a bleeding tendency. However, viscoelastic coagulation assays (VCA) like Rotational Thromboelastometry (ROTEM) and Thromboelastography (TEG) depict a hypercoagulable state. Therefore, hemostatic interventions should not be indicated according to deranged CCA results, but only in case of clinically relevant bleeding plus indicative VCA results. Massive blood loss mainly results from surgical excision of burn wounds. VCAs seem to be capable of guiding target-oriented coagulation management in this context. Owing to the increased thromboembolic risk, it appears rational to individualize pharmacologic venous thromboembolism prophylaxis by using sensitive laboratory tests and drug monitoring. Studies evaluating the use of new VCA test modifications are highly warranted and may substantially improve outcome in this difficult-to-treat patient population.
Keywords: burn injury; viscoelastic tests; Rotational Thromboelastometry; Thromboelastography; point of care